A Formal Assisted Approach for Modeling and Testing Security Attacks in IoT Edge Devices - Bhanpurawala, Alifiya (2023)
A Master of Science thesis in Computer Engineering by Alifiya Bhanpurawala entitled, “A Formal Assisted Approach for Modeling and Testing Security Attacks in IoT Edge Devices”, submitted in November 2023. Thesis advisor is Dr. Khaled El-Fakih. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).